2021
DOI: 10.1007/s40313-021-00740-x
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Hybrid-Electric Propulsion: Development Trends, Challenges and Opportunities

Abstract: The present work is a survey on aircraft hybrid electric propulsion (HEP) that aims to present state-of-the-art technologies and future tendencies in the following areas: air transport market, hybrid demonstrators, HEP topologies applications, aircraft design, electrical systems for aircraft, energy storage, aircraft internal combustion engines, and management and control strategies. Several changes on aircraft propulsion will occur in the next 30 years, following the aircraft market demand and environmental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 82 publications
(188 reference statements)
0
17
0
3
Order By: Relevance
“…With such structures, the power generated by the gas turbine is converted to electrical power for longer distance transmission, whereas the motor-driven fans or propellers can be distributed to the wings and rear of the fuselage; moreover, they can be independently controlled by power electronic devices. However, all these patterns must be investigated further in terms of several aspects, especially the energy density of batteries, the efficiency of electrical machines, and optimization of the powertrain structure [84]. Boundary layer ingestion (BLI) is another potential HEA.…”
Section: O U T L O O Kmentioning
confidence: 99%
See 1 more Smart Citation
“…With such structures, the power generated by the gas turbine is converted to electrical power for longer distance transmission, whereas the motor-driven fans or propellers can be distributed to the wings and rear of the fuselage; moreover, they can be independently controlled by power electronic devices. However, all these patterns must be investigated further in terms of several aspects, especially the energy density of batteries, the efficiency of electrical machines, and optimization of the powertrain structure [84]. Boundary layer ingestion (BLI) is another potential HEA.…”
Section: O U T L O O Kmentioning
confidence: 99%
“…In addition, considering that the combustion engines are supposed to be replaced with power electronic devices and electrical machines on HEA and FEA, the thermal management system can be another main concern because power electronic devices tremendously increase temperature. Moreover, they are all inside the aircraft; this differs from conventional aircraft in which the combustion engines are outside and can directly release heat to the atmosphere [84]. To deal with heat dissipation inside the aircraft, Meredith [94] reported that the correct design of the radiator can benefit aircraft propulsion by utilizing waste thermal energy to offset the radiator drag or the Meredith effect.…”
Section: O U T L O O Kmentioning
confidence: 99%
“…It offers an additional advantage, the availability of electric backup in engine failure, allowing for a few minutes of extra endurance after failure occurrence. Moreover, the electric power source represents a useful assist for the thermal engine during high power request flight phases: in parallel architecture, the engine could be operated at its nominal power, and additional power could be supplied from electric motors during take-off or climb, while excess engine power could be spent in charging the batteries during the cruise (Rendón, Sánchez R., Gallo M., & Anzai, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A way to overcome the weight problem is to migrate to a hybrid electric aircraft (HEA) or a more electric aircraft (MEA) [4]. Doing so could take advantage of the high energy density of conventional fuel-powered gas turbine engines [4,5], and the flexibility of electrical motors [6,7]. The design of electric aircraft employs a lot of aerodynamics concepts.…”
Section: Introductionmentioning
confidence: 99%